2007
DOI: 10.1111/j.1600-0420.2007.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal injections and volume changes on intraocular pressure: clinical results and biomechanical model

Abstract: ABSTRACT.Purpose: Intravitreal injections are used extensively to treat retinal diseases. Performing an intravitreal injection increases intraocular volume by the amount of fluid brought into the eye. Whether this influences intraocular pressure (IOP) was investigated here. Methods: A biomechanical model relying on 3-dimensional elasticity theory was developed to determine the short-term effect of volume changes on IOP. We calculated the effect for intravitreal injections of 0.1 ml in myopic, emmetropic and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
23

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 19 publications
5
63
0
23
Order By: Relevance
“…These include sheer volume increase inside the eye, which is in turn related to vitreous reflux and needle bore size, 5 as well as the actual volume injected. 5,13 This study found no significant reduction in IOP immediately after injection between the control vs treatment group, which further supports the idea of a sheer volume-related pressure effect immediately after injection. Measurement of the IOP just before injection, although not done in this study, may have been useful to confirm the efficacy of pre-injection acetazolamide administered 60-90 min earlier in the treatment arm.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These include sheer volume increase inside the eye, which is in turn related to vitreous reflux and needle bore size, 5 as well as the actual volume injected. 5,13 This study found no significant reduction in IOP immediately after injection between the control vs treatment group, which further supports the idea of a sheer volume-related pressure effect immediately after injection. Measurement of the IOP just before injection, although not done in this study, may have been useful to confirm the efficacy of pre-injection acetazolamide administered 60-90 min earlier in the treatment arm.…”
Section: Discussionsupporting
confidence: 73%
“…13 A positive correlation has been found between rigidity coefficient and age, 14 which suggests that a similar volume injected into an older more rigid eye might induce a higher IOP. 13 Although worth considering, the phakic status and status of vitreous/posterior hyaloid face were not evaluated in this study.…”
Section: Discussionmentioning
confidence: 93%
“…The change of the scleral thickness under intraocular pressure (IOP) well agree with clinical data on decrease of scleral thickness in primary open-angle glaucoma (POAG) [8].…”
Section: Discussionsupporting
confidence: 71%
“…15 Erken dönemde saptanan akut ve genellikle geçici özellikteki yükselmelerin ise ilacın özelliklerinden ziyade, göz içindeki hacmin ani artışı sonucunda ortaya çıktığı düşünülmektedir. 16 İntravitreal bevacizumab enjeksiyonuna bağlı erken dönem GİB değişikliklerini değerlendirmeyi hedeflediğimiz çalışmamızda; hastalarımıza uygulanan 0,05 ml bevacizumab sonrası ortalama GİB'in birinci dakikada 17,91±3,7 mmHg düzeyinden, 34,58±13,5 mmHg düzeyine yükseldiği saptanmıştır. Cacciamani ve ark.17 benzer şekilde intavitreal bevacizumab enjeksiyonu öncesi ölçülen ortalama GİB'in 16,52±3,32 mmHg olduğunu, enjeksiyon sonrası birinci dakikada bu değerin 38,44±7,92 mmHg'ye yükseldiğini bildirmişlerdir.…”
Section: Discussionunclassified